A parametrized variational principle of nonlinear piezoelectricity - He, Ji-Huan (Computer Assisted Methods in Engineering and Science; Vol 10 No 3 (2003), 2023)
The variational theory is the theoretical basis of the finite element method, meshfree particle methods and other modern numerical techniques. The present paper establishes a family of variational principles for nonlinear piezoelectricity. A new constitutive relation is suggested, which is deduced as a stationary condition of a generalized variational principle.